Konstruksi Moralitas Yang Rasional Dalam Hukum - Victor Imanuel Nalle (SAPIENTIA ET VIRTUS, 2015)
Law in the context of modernity, as an instrument of social engineering, often slammed with the concept of law as a moral order that was carried by the laws of nature. Law as an instrument of social engineering by adherents of positivism is seen as more rational, whereas the natural law morality tends to be paralleled by religious morality. This is due to the natural law theory of Thomas Aquinas dominated philosophy is heavily influenced by the theological aspects. Yet morality in modern law is not attached to religious doctrine or dogma. Morality in modern law it can be rationalized by human reason. Thus the law does not need to be sterilized of morality as the opinion of positivism. Expediency and fairness in the law it can eventually rebuilt on a rational morality.